Desarrollo de un sistema informático en ambiente web y móvil para automatizar el proceso de ventas del comisariato América aplicando técnicas de Business Intelligence - Cuji Chiliquinga, Bryan Saúl (2022)
We live in a world where technology has advanced to a great level. However, new ideas always arise, and this technology is progressing even more, that is why this degree project proposes a computer system developed in web and mobile environment, which the Commissary America will use; this will be done by applying Business Intelligence; this technique allows us to transform the data obtained in information, so that the decision making process can be improved, because, in general terms what is proposed is a form of efficient e-commerce, this means, to make sales digitally, offering promotions and discounts, thus avoiding material and economic losses, as well as, offering the user different payment methods, according to their needs, regarding the use of the system an administrative panel is implemented which allows managing all existing processes according to the user's role. Currently, there are two roles, the user and the administrator. The tools used to develop this project were: Visual Studio Code and Android Studio. These are the development environments used to maintain version control. GitLab was used, as for the frameworks, the Model View Controller, Bootstrap and CSS were used. The database management system is XAMPP which works in conjunction with the database engine PhpMyAdmin. Finally, as for the methodology, the Kanban methodology was chosen due to its visual method of project management.